Clinical investigation of athletes with persistent fatigue and/or recurrent infections. Issue 1 (29th January 2004) - Reid, V L; Gleeson, M; Williams, N; Clancy, R L
Abstract : Objective: To investigate whether underlying medical conditions contribute to the fatigue and high incidence of infections that can occur during repeated intense training. Method: Forty one competitive athletes (22 male, 19 female) with persistent fatigue and/or recurrent infections associated with performance decrements had a thorough medical examination and a series of clinical investigations to identify potential medical causes. Results: Conditions with the potential to cause fatigue and/or recurrent infections were identified in 68% of the athletes. The most common were partial humoral immune deficiency (28%) and unresolved viral infections (27%). Non-fasting hypoglycaemia was common (28%). Other conditions included allergic disease (15%), new or poorly controlled asthma (13%), upper airway dysfunction (5%), sleep disorders (15%), iron depletion (3%), and one case of a thyroid disorder. A positive antinuclear antibody was detected in 21% of the athletes, without any clinical evidence of autoimmune disorders. Evidence of Epstein-Barr virus reactivation was detected in 22% of the athletes tested. Conclusions: Athletes with recurrent infections, fatigue, and associated poor performance may benefit from a thorough investigation of potentially reversible underlying medical conditions, especially when these conditions cause disruption to training and competition. Unresolved viral infections are not routinely assessed in elite athletes, but it may be worth considering in those experiencing fatigue and performing poorly.